Outpatient follow-up and use of medications for opioid use disorder after residential treatment among Medicaid enrollees in 10 states. (1st December 2022) - Cole, Evan S.; Allen, Lindsay; Austin, Anna; Barnes, Andrew; Chang, Chung-Chou H.; Clark, Sarah; Crane, Dushka; Cunningham, Peter; Fry, Carrie E.; Gordon, Adam J.; Hammerslag, Lindsey; Idala, David; et al.
Abstract: Background: Follow-up after residential treatment is considered best practice in supporting patients with opioid use disorder (OUD) in their recovery. Yet, little is known about rates of follow-up after discharge. The objective of this analysis was to measure rates of follow-up and use of medications for OUD (MOUD) after residential treatment among Medicaid enrollees in 10 states, and to understand the enrollee and episode characteristics that are associated with both outcomes. Methods: Using a distributed research network to analyze Medicaid claims data, we estimated the likelihood of 4 outcomes occurring within 7 and 30 days post-discharge from residential treatment for OUD using multinomial logit regression: no follow-up or MOUD, follow-up visit only, MOUD only, or both follow-up and MOUD. We used meta-analysis techniques to pool state-specific estimates into global estimates. Results: We identified 90, 639 episodes of residential treatment for OUD for 69, 017 enrollees from 2018 to 2019. We found that 62.5% and 46.9% of episodes did not receive any follow-up or MOUD at 7 days and 30 days, respectively. In adjusted analyses, co-occurring mental health conditions, longer lengths of stay, prior receipt of MOUD or behavioral health counseling, and a recent ED visit for OUD were associated with a greater likelihood of receiving follow-up treatment including MOUD after discharge. Conclusions: Forty-seven percent of residential treatment episodes for Medicaid enrollees are not followed by an outpatient visit or MOUD, and thus are not following best practices. Highlights: Little is known about rates of follow-up after residential treatment. Among Medicaid enrollees, 46.9% received no follow-up within 30 days of discharge. Rates of any follow-up or MOUD within 30 days ranged from 44.8% to 64.3% across 10 states. Prior treatment engagement was associated with a greater likelihood of follow-up.